2008
DOI: 10.1111/j.1742-4658.2008.06291.x
|View full text |Cite
|
Sign up to set email alerts
|

Transduced human PEP‐1–heat shock protein 27 efficiently protects against brain ischemic insult

Abstract: Reactive oxygen species contribute to the development of various human diseases. Ischemia is characterized by both significant oxidative stress and characteristic changes in the antioxidant defense mechanism. Heat shock protein 27 (HSP27) has a potent ability to increase cell survival in response to oxidative stress. In the present study, we have investigated the protective effects of PEP‐1–HSP27 against cell death and ischemic insults. When PEP‐1–HSP27 fusion protein was added to the culture medium of astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 53 publications
3
56
0
Order By: Relevance
“…For example, HSP27 can inhibit apoptosis by reducing caspase activity (33), decrease cytochrome c release from mitochondria (34), and/or inactivate the apoptosis signal-regulating kinase 1/JNK prodeath signaling cascade (17). A number of previous studies reported the neuroprotective effects of HSP27 against cerebral I/R injury when globally expressed in the brain (15)(16)(17)22). However, the anti-cell death properties of HSP27 are unlikely to directly contribute to protection against BBB leakage 1-3 h after I/R, because cell death is not apparent until some hours after this early stage in postischemic ECs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HSP27 can inhibit apoptosis by reducing caspase activity (33), decrease cytochrome c release from mitochondria (34), and/or inactivate the apoptosis signal-regulating kinase 1/JNK prodeath signaling cascade (17). A number of previous studies reported the neuroprotective effects of HSP27 against cerebral I/R injury when globally expressed in the brain (15)(16)(17)22). However, the anti-cell death properties of HSP27 are unlikely to directly contribute to protection against BBB leakage 1-3 h after I/R, because cell death is not apparent until some hours after this early stage in postischemic ECs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, the level of HSP27 is extremely low in the brain; however, HSP27 expression is transiently induced in brain glial cells and/or ECs at 24 h or later following cerebral I/R (14). Previous studies by our and other groups demonstrated robust neuroprotective effects of HSP27 overexpression against I/R brain injury (15)(16)(17)(18), which were largely credited to its antiapoptotic actions. However, HSP27 exerts additional actions on ECs (14).…”
mentioning
confidence: 95%
“…The PEP-1-SOD1 (wild & mutant) and PEP-1-HSP27 expression vectors were constructed as previously described (27,28). Two oligonucleotide primers were synthesized based on the cDNA sequence of human HSP27 and were ligated into a NdeI-XhoI-digested pET-15b vector for PCR amplification.…”
Section: Expression and Purification Of Pep-1-hsp27 Fusion Proteinsmentioning
confidence: 99%
“…Construction, expression and purification of the PEP-1-HSP27 and PEP-1-SOD1 fusion proteins are all previously described (27,28). Briefly, PEP-1-HSP27 and PEP-1-SOD1 fusion proteins were purified following the induction of expression using a Ni 2+ -nitrilotriacetic acid Sepharose affinity column and PD-10 http://bmbreports.org BMB reports column chromatography.…”
Section: Purification Of Pep-1-hsp27 and Pep-1-sod1 Fusion Proteinsmentioning
confidence: 99%
“…Protein transduction technology based on small domains called protein transduction domains (PTDs) and cell penetrating peptides (CPPs) has been used to deliver exogenous protein into cultured cells and animal models (2)(3)(4)(5)(6)(7). Many research groups have demonstrated the efficacy of protein transduction technology for protein therapy strategies as well as drug delivery, although the exact mechanism of transduction remains unclear (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Although various proteins have been developed for protein therapy, protein transduction technology has several limitations such as transduction efficiency.…”
Section: Introductionmentioning
confidence: 99%